2012
DOI: 10.4149/neo_2013_019
|View full text |Cite
|
Sign up to set email alerts
|

Pathological implication and function of Bcl2-inhibitor of transcription in ovarian serous papillary adenocarcinomas

Abstract: The Bit-1 protein appears to be a part of the integrin-specific signaling pathway involved into anoikis. When Bit1 is released from the mitochondria into the cytoplasm it can elicit caspase-independent apoptosis. The expression of Bit1 in 78 serous papillary adenocarcinomas and 78 normal epithelial ovarian tissue specimens was analyzed by immunohistochemistry. We also investigate Bit1 function by transfection. Bit1 was expressed in 100% and 33.3% of ovarian cancers and normal epithelial tissues, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In ovarian serous papillary adenocarcinomas, low PTRH2 protein expression significantly correlates with higher histologic grade and poorer clinical prognosis. In vitro, cytosolic-PTRH2 protein overexpression in Caov-3 cells decreases cell viability 80 . PTRH2 is also detected in sera of patients with serous papillary adenocarcinomas 81 .…”
Section: Ptrh2 Is Downstream Of Estrogen Receptor and Signals Throughmentioning
confidence: 99%
“…In ovarian serous papillary adenocarcinomas, low PTRH2 protein expression significantly correlates with higher histologic grade and poorer clinical prognosis. In vitro, cytosolic-PTRH2 protein overexpression in Caov-3 cells decreases cell viability 80 . PTRH2 is also detected in sera of patients with serous papillary adenocarcinomas 81 .…”
Section: Ptrh2 Is Downstream Of Estrogen Receptor and Signals Throughmentioning
confidence: 99%
“…Only the mutant clones carried the deletion of chr17p13.1 and the duplications of chr17q23.1 and the X chromosome. The only gene contained within the chr17q23.1 region was PTRH2, which has been associated with cancer and apoptosis [31][32][33], but whose role in tumorigenesis is not well understood. Both duplications and deletions of the X chromosome are frequently observed in human tumors, but are also correlated with increasing age [34,35], leading some to conclude that X chromosome numerical aberrations were likely to be a secondary event, and not important in the pathogenesis of cancers [35].…”
Section: Establishment Of Clonal Wa09 Hesc Sublines With Andmentioning
confidence: 99%
“…Therefore, combinations of Bit1, Bcl-2, and MMP2 will be a new strategy for distinguishing the subtypes of ESCC and EA. Recently, data reported that Bit1 expression level in ovarian carcinoma was markedly higher than that in the normal tissues; 15 in addition, Bit1 expression contributed to the survival of cervical cancer, 29 implying Bit1 functions as an oncogene in the ovarian and cervical cancers. However, Bit1 depletion increased cell adhesion and migration of breast carcinoma, suggesting Bit1 acts as a tumor suppressor in breast carcer.…”
Section: Discussionmentioning
confidence: 99%